Factors affecting expression of estrus measured by activity monitors and conception risk of lactating dairy cows - Madureira, A. M. L. [UNESP]; Silper, B. F.; Burnett, T. A.; Polsky, L.; Cruppe, L. H.; Veira, D. M.; Vasconcelos, J. L. M. [UNESP]; Cerri, R. L. A. (Elsevier B.V., 2015)
The objective of this study was to determine risk-factors affecting increase in physical activity during estrus and pregnancy per artificial insemination (P/AI) in lactating dairy cows. Cows were monitored continuously by 2 automated activity monitors [a collar-mounted accelerometer (HT; Heatime, SCR Engineers, Netanya, Israel) and a leg-mounted pedometer (BO; Boumatic Heat-seeker-TX, Boumatic Dairy Equipment, Madison, WI)]. When an increase in activity was detected, body condition score (BCS) and blood samples were collected, ovaries were scanned by ultrasonography, and, if the cow was eligible for breeding, artificial insemination was performed. Milk production and health-related data were recorded throughout the experimental period. Pregnancy diagnosis was performed at 42 +/- 7 d of gestation. Data were analyzed using Pearson correlation, ANOVA, and logistic regression. A total of 1,099 true events of estrus from 318 lactating Holstein cows were recorded, averaging 3.46 +/- 1.1 events per cow. Positive predictive value for estrus episodes detected by the HT and BO systems were 89.6 and 85.5%, respectively. Mean peak activity at estrus (PA) recorded by the HT system was 71.6 +/- 20.7 index-value, and 334.3 +/- 155.7% relative increase by the BO system. Compared with primiparous, multiparous cows expressed estrus with lower PA (69.3 +/- 0.8 vs. 75.9 +/- 1.1 index for HT; 323.9 +/- 6.0 vs. 354.8 +/- 8.48% for BO) and shorter duration (DU; 10.7 +/- 0.2 vs. 12.0 +/- 0.3 h); DU was measured by HT only. Lower BCS was associated with decreased PA measured by both systems, estrus DU, and P/AI. Peak activity was weakly correlated with milk production on the day of artificial insemination (r = -0.20); however, when categorized into quartiles, the highest-yield cows had lower PA and DU. Follicle diameter was not correlated with PA or DU, but cows with greater concentrations of estradiol had higher PA. Cows with greater PA in both systems had greater P/AI than those with lower PA (36.5 vs. 24.6% for HT, 33.5 vs. 21.4% for BO). In conclusion, measurements of estrus events captured by automated activity monitors are correlated with BCS,' parity, and secondary behavior signs related to estrus. Surprisingly, estrus intensity and duration were only weakly correlated with milk production, preovulatory follicle diameter, and concentrations of estradiol at estrus. Cows that had measurements of high-intensity estrus were significantly more fertile than low-intensity estrus.
Keywords: automated activity monitor; pregnancy per artificial insemination; milk production; estrus expression